THE ROLE OF INTERNATIONAL LEGAL INSTRUMENTS IN THE FORMATION OF A SECURITY ENVIRONMENT - Hrichanichenko, Vladyslav (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2024)
The article draws attention to the existence of an urgent need to reform all spheres of life and functioning of the state, which will contribute to the formation of a safe environment. The issues of this issue become especially relevant after the full-scale invasion of the territory of Ukraine on February 24, 2022, which is due to the complexity of the international situation of our country, the conduct of active hostilities, the spread of international terrorism, the aggravation of threats to the interests of individual citizens, society and the state as a whole, which requires the development effective measures to ensure national security It was determined that the security environment is a set of social, material, geopolitical, political and diplomatic conditions that ensure the safe and effective existence of individuals and legal entities, society and the state. In addition, the provisions of certain international legal acts, which regulate the issue of ensuring the safe existence of the international community in the information environment, protection against terrorism, as well as preventing the violation of any international obligations by other states, are analyzed. It has been established that responsibility for violation of international obligations, including through negative impact or damage to the security environment at the international level, is provided only in the case of enshrining the relevant provisions in the norms of international legal acts. According to the results of the study of the role of international legal instruments in the formation of the security environment, it was established that to date there is no single international legal act, which defines the instruments of the formation of the security environment and the methods of their use, and all measures in this field are carried out on the basis of the provisions of separate international treaties. In this connection, the adoption of a separate legal act on the formation of a security environment and the holding of additional negotiations at the international level is proposed.